ChemInform Abstract: Platinum(II) Catalyzed Enantioselective Cycloisomerizations of 3‐Hydroxylated 1, 5‐Enynes. Issue 46 (24th October 2013) - Zhang, Yang; Jullien, Helene; Brissy, Delphine; Retailleau, Pascal; Voituriez, Arnaud; Marinetti, Angela
Abstract Screening experiments show that a chiral BINOL‐derived Pt‐catalyst gives the best results in the cycloisomerizations of 1, 5‐enynes.